Internalization of Religious Moderation Values Through Madrasah Culture - Maskanah, Ulfa; Rifa’i, Ahmad Suzaki; Nuriyah, Addina Silky; Afwadzi, Benny (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v9i1.3135, 2024)
Religious moderation, considered to have resonated in the world of education, has found several problems. Based on several facts, there is an increase in intolerance among high school students. Therefore, internalizing the value of religious moderation becomes the main topic of discussion. By emphasizing internalization through madrasah culture, this study aims to contribute to developing an education model that prioritizes academic aspects and balanced moral and social aspects. This study uses a qualitative approach, collecting data from interviews, observations, and documentation studies. Data analysis uses the Miles, Huberman, and Saldana analysis techniques. The validity of the data is maintained through the credibility of triangulation of sources and methods. This study shows that first, the culture of MA Mazro’atul Ulum has a salaf character; Second, the process of internalizing the value of religious moderation through culture is using the habituation method; Third, the impact of internalizing religious moderation for students can form a Positive Character, can strengthen identity and self-awareness, and students are more prepared to live a diverse social life. This study proposes a model for internalizing the value of religious moderation through madrasah culture. For students to more easily internalize the values of religious moderation, the habituation method has historically been recorded as the most successful method in forming students’ personalities, including in instilling the values of religious moderation.